Genome Sequence of a Novel HIV-1 Circulating Recombinant Form (CRF64_BC) Identified from Yunnan, China - Hsi, Jenny (Mary Ann Liebert, Inc., 2014)
We report a novel HIV-1 circulating recombinant form (CRF64_BC) that was isolated from five epidemiologically unlinked HIV-infected persons in Yunnan province. CRF64_BC was composed of subtype B and subtype C, with five short subtype B segments inserted into the subtype C backbone. Phylogenetic analysis demonstrated that the C subregion was correlated with the India C lineage, which was transmitted into China in the early 1990s. The evolutionary history of the B subregion was not as clear as the C subregion, as the short length of this region yielded poor phylogenetic results. Dehong is considered the epicenter of HIV-1 in China, and recombinant strains such as CRF07_BC and CRF08_BC, which also originated from this region, have spread widely in China. The newly emerged CRF64_BC increases the complexity of the HIV epidemic in China and complicates the development of subtype-specific tools against HIV transmission.